CO2 injection-induced fracturing in naturally fractured shale rocks. (15th November 2017) - Wang, Lei; Yao, Bowen; Xie, Haojun; Winterfeld, Philip H.; Kneafsey, Timothy J.; Yin, Xiaolong; Wu, Yu-Shu
Abstract: Niobrara shale cubes of 20 cm from Colorado were employed to investigate gas and supercritical CO2 injection-induced fracturing in naturally fractured caprocks of deep aquifers/depleted reservoirs and fractured shale reservoirs. Under tri-axial stresses, gas or supercritical CO2 was injected into the center of the cubes to induce fracturing. Real-time pressure and temperature, acoustic wave, pressure decay, fracture coloring, and gas fracturing were used to characterize the fracturing process and fracture morphology. Without pore pressure, CO2 injection-induced fracturing occurred and completed instantly, accompanied by an evident temperature drop. Strongly bonded fractures barely affected transverse fracture propagation, whereas weakly bonded or open fractures arrested the injected fluid first and then allowed it to generate new fractures perpendicular to the minimum horizontal stress. Breakdown pressures for cubes with preexisting fractures using gas and supercritical CO2 are much lower than both poroelastic predictions and slick-water fracturing pressure, and some are even lower than the minimum horizontal stress. This is attributed to unconformable preexisting fractures and the low viscosity of CO2 . Moreover, decreasing tri-axial stress levels and increasing stress differences tend to lower the breakdown pressure. This study is instructive for understanding and tackling geomechanical issues related to CO2 geological storage and fracturing of shale reservoirs. Highlights: ScCO2 injection-induced fracturing in shale cubes is monitored and characterized. Calcite-filled fractures barely affect transverse fracturing induced by scCO2 . Weakly bonded preexisting fractures divert CO2 injection-induced fracturing. Breakdown pressures of gas and scCO2 are much lower than that of slick-water.